Therapeutic benefits of hiking / Nazima Versay Kudus, Muhammad Aiman Abdul Halim and Nur Ilianis Adnan - Versay Kudus, Nazima; Abdul Halim, Muhammad Aiman; Adnan, Nur Ilianis (Academy of Language Studies, 2022)
During the Movement Control Order (MCO), the government had put its citizens under self-quarantine. Thankfully, the MCO has been lifted and fellow Malaysians can now enjoy previously prohibited outdoor activities such as hiking because this activity provides you with various health benefits.